The Effect of Financing Diversification on Financing Risk: The case of the Islamic Rural Banks in West and East Java Province - Widarjono, Agus; Hapsari, Putri Nela (Jurnal Analisis Bisnis Ekonomi, 2024)
The main problem faced by Islamic rural banks (IRBs) in Indonesia is the high level of non-performing financing (NPF). This paper analyzes the factors that influence NPF by focusing on the effect of financing diversification based on financing contracts. The IRBs being studied are banks located in West Java and East Java which constitute 34% of the total IRBs in Indonesia. The research period is from 2013-2022 using quarterly data and unbalanced panel data. The estimation method used is panel regression. The results document that the concentration of financing based on contracts reduces the NPF. Apart from that, the size of the bank, high capital, and stability will also reduce NPF. However, financing and operational efficiency do not affect NPF. COVID-19, which has caused a decline in Indonesia's economic growth, has increased the NPF. The policy implication of these findings is that IRBs must focus on certain financing contracts to reduce the risk of bad financing instead of disbursing all financing contracts.